2002
DOI: 10.3390/s20800347
|View full text |Cite
|
Sign up to set email alerts
|

Gamma Radiation Dosimetry Using Tellurium Dioxide Thin Film Structures

Abstract: Thin films of Tellurium dioxide (TeO2) were investigated for γ-radiation dosimetry purposes. Samples were fabricated using thin film vapour deposition technique. Thin films of TeO2 were exposed to a 60Co γ-radiation source at a dose rate of 6 Gy/min at room temperature. Absorption spectra for TeO2 films were recorded and the values of the optical band gap and energies of the localized states for as-deposited and γ-irradiated samples were calculated. It was found that the optical band gap values were decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(25 citation statements)
references
References 24 publications
3
22
0
Order By: Relevance
“…They, however, did not report for higher radiation doses. A comparison of the present results with those of Arshak and Korostynska (2002) clearly shows that the rate of increase of the energy width with radiation dose for thicker films is much lower than that for thinner films. Obviously, thin films are more sensitive than thick films.…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…They, however, did not report for higher radiation doses. A comparison of the present results with those of Arshak and Korostynska (2002) clearly shows that the rate of increase of the energy width with radiation dose for thicker films is much lower than that for thinner films. Obviously, thin films are more sensitive than thick films.…”
Section: Resultssupporting
confidence: 58%
“…Whenever gamma radiation interacts with the thin film, induced defects will be formed and the density of the localized states increases resulting in increase in the energy width of the band tails of localized states. Arshak and Korostynska (2002) reported that the energy width of the band tails of localized states for the TeO 2 thin films of thickness, 50 nm, increased with the increase of radiation dose up to a value of 36 Gy. They, however, did not report for higher radiation doses.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] On the other hand, they have several problems to overcome, such as a lack of sensitivity and very low sensitivity to low gas concentrations at room temperature. The development of highly selective and controllably-sensitized devices remains a challenge.…”
Section: Introductionmentioning
confidence: 99%
“…Tellurium dioxide (TeO 2 ) is an important material in both amorphous as well as crystalline form and finds application in active optical devices in particular, a huge hyper-susceptibility, deflectors, modulators, c-ray detectors, and gas sensors because of its high acousto-optic figure of merit, chemical stability, and mechanical durability [1][2][3][4][5][6]. It is also not hygroscopic and has superior physical properties such as high dielectric constant and low melting point (800°C) [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%